PELATIHAN DAN KOMPETISI GOARA-GOARA TINGKAT INTERNASIONAL DI UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA TAHUN 2026 - Slamet Santoso; Shodiq Hutomono; Teguh Andibowo; Teguh Santosa; Erik Teguh Prakoso; Faridha Isnaini (Jurnal Pengabdian Masyarakat FKIP UTP, 2026)
Technological advancements should be leveraged to revitalize traditional games, making them more engaging and ensuring their preservation for future generations. However, technology can also negatively impact traditional games, as children today often no longer play them. Driven by a passion for culture, academics have felt compelled to preserve local wisdom and traditional games. Efforts to conserve and reintroduce these nearly extinct traditional games have taken the form of international-level training sessions and competitions for "Goara-Goara." Goara-Goara is a composite of Indonesian traditional sports and games, integrated into a single, unique, engaging, and enjoyable new game. This innovative game incorporates seven to eight traditional activities, such as *rangku alu* (bamboo dance), sack racing, progressive jump rope, *suda manda* (hopscotch), bamboo stilts, *boy-boyan* (ball-and-tile game), and—optionally—bamboo climbing. The project was implemented in three stages: 1) promoting Goara-Goara via social media and sharing information with training organizers; 2) conducting a 10-hour Goara-Goara training session; and 3) hosting an international Goara-Goara competition. Participants hailed from 11 countries—Bangladesh, Afghanistan, Pakistan, Sudan, Yemen, the Philippines, The Gambia, Uganda, Timor-Leste, Japan, and Indonesia—with a total of 175 participants. These training and competition activities were organized and funded by the UTP Institute for Research and Community Service, in collaboration with the Office of International Affairs and with support from the UTP PPG FKIP (Teacher Professional Education Program).